Properties of self-consolidating palm oil fuel ash concrete - Safiuddin, M.; Rahman, M.M.; Salam, M.A.; Md.Isa, M.H.; Jumaat, Mohd Zamin (Advanced Science Letters, 2012)
This paper presents the fresh and hardened properties of self-consolidating palm oil fuel ash concretes. Different self-consolidating concrete mixtures were produced based on the water/binder ratios of 0.40, 0.50 and 0.60. Palm oil fuel ash was incorporated in concretes substituting 0, 5, 10, and 15 of normal portland cement by weight. The freshly mixed concretes were tested for filling ability, passing ability, and segregation resistance. The hardened concretes were tested for compressive strength, ultrasonic pulse velocity, water absorption, and permeable porosity. The effects of water/binder ratio and palm oil fuel ash content on the properties of concrete were observed. The correlations of compressive strength with ultrasonic pulse velocity and permeable porosity were also indentified. According to test results, the compressive strength and ultrasonic pulse velocity decreased while the water absorption and permeable porosity increased with higher water/binder ratio. Palm oil fuel ash was not effective in improving the hardened properties of concretes produced with the water/binder ratios of 0.50 and 0.60. However, significant improvement was observed when palm oil fuel ash was used in concrete with the water/binder ratio of 0.40. The optimum palm oil fuel ash content was 5 in the context of present study. Â© 2012 American Scientific Publishers. All rights reserved.